Prevalence and Main Clinical Characteristics of Fully Vaccinated Patients Admitted to Hospital for Delta Variant COVID-19 - Vassallo, Matteo; Clement, Nicolas; Lotte, Laurene; Manni, Sabrina; Sindt, Audrey; Bertrand, Pierre M.; Durant, Jacques (Frontiers in Medicine, 2022)
Objectives: The Delta variant of the novel beta coronavirus responsible for the current coronavirus pandemic (Covid-19) spread across Europe during the summer of 2021. Little is known of vaccine efficacy on this variant. Our aim was to study the prevalence and clinical characteristics of fully vaccinated subjects admitted to hospital for Delta variant Covid-19 Methods: We identified patients admitted to Cannes hospital for Delta-variant-related Covid-19 infection from July to September 2021. Their main demographic parameters, inflammatory markers and clinical characteristics were recorded. Differences between fully vaccinated subjects and unvaccinated or incompletely vaccinated individuals were analyzed. Results: We included 126 patients (57% male, mean age 64 years, mean delay since symptoms onset 7.8 days). Among admitted patients, 94 (75%) were not vaccinated, 11 (8%) incompletely so and 21 (17%) were fully vaccinated. Fully vaccinated patients were older (77 vs 61 vs 62 years, p = 0.003) and days since symptoms onset were fewer (5.9 vs 8.0 vs 9.3 days, p = 0.035) than unvaccinated or incompletely vaccinated patients, respectively. Severe pneumonia was less frequent among completly vaccinated subjects (67% vs 84% vs 100%), while rates of transfer to the ICU, mechanical ventilation or death did not differ. Thirteen fully vaccinated patients underwent a thoracic CT scan, revealing involvement of lung parenchyma in four of them. Discussion: Prevalence of hospitalization for Delta-variant Covid-19 in fully vaccinated subjects was low and, despite their age and comorbid conditions, these patients had a high rate of favourable outcome.